Sejarah Titik, Harakat, dan Ilmu Rasm Mushaf - Fathur Rohman Ansyari; Rahmi Damis (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
In the early days of the writing of the Qur'an, the existing mushaf only included consonants without any period or harakat. This causes confusion in reading the Qur'an, especially for readers who have not mastered Arabic in depth. To overcome this problem, Al-Khalil bin Ahmad al-Farahidi, an Arabic linguist, introduced the point system in the 2nd century Hijri. The methodology used in this study is qualitative using descriptive analysis with library research in collecting the data. The result of this research is that Fawatiḥ al-Suwar is the opening part of the surahs in the Qur'an which consists of various forms, such as ḥurūf muqaṭa'ah, expressions of praise, oaths, exclamations, or thematic affirmations. The writing of the Qur'an, both in terms of points, harakat, rasm mushaf, and fawa tih al-suwar, has a very important role in maintaining the accuracy and uniformity of the reading of Divine revelation. The rasm mushaf established during the time of Caliph Uthman bin Affan became a uniform standard for writing the Qur'anic mushaf, adopting the use of points and harakat, and introducing deviations from the standard Arabic rules to maintain uniformity of reading and authenticity of the text. Overall, every element in the writing of the Qur'an, be it dots, harakat, rasm mushaf, or fawatihal-suwar is an integral part that not only makes it easier to read and pronounce, but also enriches our understanding of the meaning contained in Divine revelation.